THE IMPACT OF CLIMATE CHANGE ON THE ECONOMY (Web of Technology: Multidimensional Research Journal, 2024)
In this article, the author expresses his views on the economic impacts of climate change in Uzbekistan, as well as the importance and measures to prevent them.